Brazilian red propolis in combination with β-lactams exerts an efficient antibacterial action over methicillin-resistant Staphylococcus aureus (MRSA) strains - Ripari, Nicolas [UNESP]; Pereira, Ana Flávia Marques [UNESP]; Júnior, Ary Fernandes [UNESP]; Rall, Vera Lúcia Mores [UNESP]; Aldana-Mejía, Jennyfer A.; Bastos, Jairo Kenupp; Sforcin, José Maurício [UNESP] (Oxford University Press (OUP), 2023)
AIMS: The antibacterial activity of red propolis extract (RPE) and brown propolis extracts (BPE) and the synergistic effect of RPE with cefoxitin (CEFO), imipenem (IMI), and ertapenem (ERTA) was evaluated in vitro against methicillin-resistant Staphylococcus aureus (MRSA) strains. METHODS AND RESULTS: MRSA ATCC 33591, community-associated (CA-MRSA) USA300, and four clinical isolates were used. A broth microdilution assay was performed to obtain inhibitory and bactericidal concentrations of BPE, RPE, CEFO, IMI, and ERTA. RPE in combination with CEFO, IMI, and ERTA was evaluated on the formation or eradication of biofilm. The bacterial relative membrane conductivity of the strains was assessed after RPE and combinations exposition. Surface/binding computational analyzes between RPE compounds and penicillin binding protein 2a (PBP2a) were performed. BPE samples had no activity against MRSA (MICs 3.2-5 g l-1; MBCs 10-15 g l-1), so the subsequent assays were carried out only with RPE and antimicrobials. RPE exerted a bacteriostatic action (MICs 0.0156-0.125 g l-1; MBCs 0.5-2 g l-1) but the combinations with IMI and ERTA showed the highest inhibition, as observed in the time-kill curve. However, the FICI index showed synergism (≥0.5) only to RPE + IMI. This combination was the most effective in inhibiting the biofilm and showed the highest values of membrane conductivity. Computational predictions indicated that RPE constituents may interact with PBP2a. CONCLUSION: RPE and RPE + IMI exerted an antibacterial and antibiofilm activity on MRSA strains probably due to membrane/wall damage and interactions with PBP2a.
Keywords: biofilm; methicillin-resistant Staphylococcus aureus; PBP2a; propolis; β-lactam antibiotics